The Effectiveness of Problem-Based Learning on Elementary Students’ Critical Thinking and Problem-Solving Skills - Vera Yuli Erviana; Bunga Divia; Munee Yiheng (The Indonesian Institute of Science and Technology Research, 2026)
The development of critical thinking and problem-solving skills is a central objective of contemporary elementary education. This study examined the effectiveness of Problem-Based Learning (PBL) in enhancing the critical thinking and problem-solving abilities of fourth-grade students within integrated IPAS instruction. A quantitative quasi-experimental design employing a nonequivalent control group pretest–posttest approach was used. The participants consisted of 46 fourth-grade students, divided into an experimental group (PBL, n = 23) and a control group (Project-Based Learning, PjBL, n = 23). Data were collected using validated pretest and posttest instruments measuring critical thinking and problem-solving skills. Descriptive and inferential analyses were conducted, including paired samples t-tests and effect size calculations using Cohen’s d. The results indicated that students in the PBL group demonstrated statistically significant improvements in critical thinking (t(22) = −7.40, p < .001, d = 1.42) and problem-solving skills (t(22) = −6.67, p < .001, d = 1.45), representing very large effects. In contrast, the PjBL group showed only modest and non-significant gains. These findings suggest that PBL is more effective than PjBL in fostering higher-order cognitive skills among elementary students. The study contributes empirical evidence supporting the integration of problem-centered learning approaches in primary education to enhance essential 21st-century skills.